Utilização de informações contextuais em um modelo de controle de acesso a informações médicas - Soares, Gerson Antunes (2007)
This work presents a boarding on the use of contextual information in a model of access control to electronic patient record (EPR). The EPR registers information on the health of the patient and the assistance given it, and has legal, secret and scientific character, being able to also include administrative and financial contents related the carried through procedures or treatments. In summary, can be said that the EPR keeps to the documents on the state of health and the cares received for an individual throughout its life. However, the availability of clinical information in computer networks raises questionings on the privacy of the patients and the integrity and confidentiality of the data. The access control is a point key to keep such requirements. The main objective in the development of this modelof access control is to provide different forms of access to information in a hospital environment, propitiating the adequacy with the pertinent legislation. To boarding proposal in this work allows to the application of politics and more specific rules of access, adding more functionality to the systems of access control. The focus of quarrel of this work deals with the use of medical information in the scope of the University Hospital of Santa Maria, and aims at to the integration of the model with modules in development in the data processing center of the institution.